2018
DOI: 10.1097/rhu.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fat-Soluble Vitamins in Osteoarthritis Management

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disease, in which metabolic imbalance in bone is observed. The pathological mechanism of metabolic imbalance is not clear yet, but the nutritional factors, particularly the vitamins, might be intrinsic to the development and progression of OA. In this review article, we have explored databases such as PubMed, Scopus, and Google Scholar articles until the beginning of 2017 and reviewed the role of fat-soluble vitamins in pathological and therapeutic aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…There are some reported nutritional factors that augment chondrocytic growth and differentiation. Lipophilic vitamins such as Vitamins A, D, E, and K [ 29 ], glucosamine and chondroitin sulfate [ 30 ], glucose and glucose-derived sugars [ 31 ], and vitamin D [ 32 ] were reported to have positive effects on chondrocytic growth and differentiation. Interestingly, a potential role for vitamin D in sleep arousals was reported [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some reported nutritional factors that augment chondrocytic growth and differentiation. Lipophilic vitamins such as Vitamins A, D, E, and K [ 29 ], glucosamine and chondroitin sulfate [ 30 ], glucose and glucose-derived sugars [ 31 ], and vitamin D [ 32 ] were reported to have positive effects on chondrocytic growth and differentiation. Interestingly, a potential role for vitamin D in sleep arousals was reported [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…As to nutritional factors which augment chondrocytic growth and differentiation, lipophilic vitamins [ 29 ], glucosamine and chondroitin sulfate [ 30 ], glucose and glucose-derived sugars [ 31 ], and vitamin D [ 32 ] were reported factors. Regarding the correlation between nutrition and mandibular growth, it was observed that murine subjects deficient in myo-inositol synthase and inositol monophosphatase exhibited pronounced mandibular retrognathism [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some nutrients and vitamins have been shown to associate with OA, Vitamin A and its derivatives retinoic acid regulate the cartilage and skeletal formation and drive OA development. 30 However, OA is the consequence of a multifaceted misbalance between synthesis and cleavage of extracellular matrix, and measuring one alone is often inadequate. These markers are primarily used in scientific research rather than clinical settings because they are small, difficult to measure, and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is thought to play a role in regulating all-trans-retinaldehyde in the human body [6]. DHRS3 is detect in the biology process of vitamin A that plays an important role in bone and cartilage metabolism, and its deficiency is implicated in the pathological process of OA [26]. In a study of rheumatoid arthritis (RA), DHRS3 was detected as one candidate genes for RA, as its expression was twice as high in the RA case group as in the control group [27].…”
Section: Discussionmentioning
confidence: 99%